Lifecycle view of managing different changes in projects. Issue 1 (5th July 2018) - Vuorinen, Lauri; Martinsuo, Miia Maarit
Abstract : Purpose: A project contractor can promote the success of a delivery project by planning the project well and following a project management methodology (PMM). However, various changes typically take place, requiring changes to the project plan and actions that deviate from the firm's established PMM. The purpose of this paper is to explore different types of changes and change management activities over the lifecycle of delivery projects. Design/methodology/approach: A qualitative single case study design was used. In total, 17 semi-structured interviews were carried out during a delivery project in a medium-sized engineering company that delivers complex systems to industrial customers. Findings: Both plan-related changes and deviations from the PMM were mapped throughout the project lifecycle. Various internal and external sources of change were identified. An illustrative example of the interconnectedness of the changes reveals the potential escalation of changes over the project lifecycle. Managers and project personnel engage in different change management activities and improvisation to create alternative paths, re-plan, catch up, and optimize project performance after changes. Research limitations/implications: The empirical study is limited to a single case study setting and a single industry. The findings draw attention to the interconnectedness and potential escalation effect of changes over the lifecycle of the project, and the need for integrated change management and improvisation actions. Practical implications: Efficient change management and improvisation at the early phase of a delivery project can potentially mitigate negative change incidents in later project phases. Changes are not only the project manager's concern; project personnel's skilled change responses are also helpful. The findings emphasize the importance of the project customer as a source of changes in delivery projects, meaning that customer relationship management throughout the project lifecycle is needed for successful change management. Originality/value: The study offers increased understanding of changes and change management throughout the project lifecycle. The results show evidence of plan-related and methodology-related changes and their interconnections, thereby proposing a lifecycle view of integrated change management and improvisation in projects.